The Use of Mobile Learning to Improve Students’ Motivation and the Achievement of Learning Outcomes - Aremu, Bamidele Victor (NIU Journal of Humanities, 2021)
The purpose of this study was to investigate the use of mobile learning (m-learning) to improve students’ motivation and the achievement of learning outcomes. In order to accomplish this, experimental research design was adopted. The participants of the study were 50 students of Federal University Oye Ekiti, Nigeria. Students’ Motivation Questionnaire (SMQ) and Students’ Learning Outcomes Test (SLOT) were the instruments used in the study. The research instruments were validated through face and content validity, while the realiability of the instruments were conducted through Cronbach Alpha and test retest which yielded 0.896 and 0.85. The collected data were analyzed through percentage and independent t-test. The findings revealed that there is significant gender difference in the motivation of the students to learn and in the achievement of learning outcomes. This study also realized that the motivation of students that were exposed to m-learning differ from the motivation of students that were not exposed to m-learning. It was recommended that m-learning should be integrated into the teaching and learning activities of tertiary institutions in Nigeria. In addition, students and lecturers at the higher level of education should be encouraged to possess m-learning devices and utilize m-learning for teaching and learning exercise. It was likewise recommended that lecturers should collaborate with computer programme designers to design m-learning based virtual classrooms. Keywords : M-learning; Students’ motivation; Learning outcomes; Educational technology